Resolve the Conflict Between Efficiency and Resilience - Ahuja, Vishal; Alan, Yasin; Arıkan, Mazhar (MIT Sloan Management Review, 2026)
Studies of the airline industry show that resilience does not have to come at the cost of efficiency. Managers in a variety of industries can meet both objectives by ensuring that operational performance metrics reflect true customer priorities; using predictive analytics and data-driven insights to allocate system buffers where they generate the most meaningful resilience benefits; and shaping the options offered to customers to improve their company’s resilience to disruptions.